2018
DOI: 10.1111/acps.12868
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐controlled hospital admission for patients with severe mental disorders: a nationwide prospective multicentre study

Abstract: Implementing PCA did not reduce coercion, service use or self-harm behaviour when compared with TAU. Beneficial effects of PCA were observed only in the before and after PCA comparisons. Further research should investigate whether PCA affects other outcomes to better establish its clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 23 publications
6
27
0
3
Order By: Relevance
“…The resulting reduction in inpatient days was 44.7%. These reductions are similar to several previous reports of PCA schemes [1], but much larger than those reported in Denmark [9]. Few patients in the current study had involuntary inpatient days and the dispersion in involuntary care before and after the PCA contract was large.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The resulting reduction in inpatient days was 44.7%. These reductions are similar to several previous reports of PCA schemes [1], but much larger than those reported in Denmark [9]. Few patients in the current study had involuntary inpatient days and the dispersion in involuntary care before and after the PCA contract was large.…”
Section: Discussionsupporting
confidence: 91%
“…In a larger Danish study, 422 patients used 1037 PCAs (with a mean of 2.5) in the year following the signing of PCA contracts, and the reduction in inpatient days from the previous year was 17. The study found no important differences between PCA patients and a propensity-matched, register-based sample of 2110 patients drawn from all Danish mental health inpatients in the same period [9].…”
Section: Introductionmentioning
confidence: 64%
“…It is proposed that a lower retinal sensitivity to light in combination with the reduced light levels in winter leads to subthreshold light input to neural circuitry and consequently to the development of seasonally occurring depressive episodes. Roecklein et al were the first to present pupillometric evidence that the melanopsin-driven pupillary responses were attenuated in patients with SAD compared to healthy controls during depressed winter phase (2). The same group showed that this impairment was not present in the remitted summer state but only in depressive winter state (4).…”
Section: Investigations Of Pupillary Responses In Depressionmentioning
confidence: 99%
“…The recent study of Berman et al published in Acta Psychiatrica Scandinavica (1) adds to a list of reports of quantifiable attenuations in the pupillary responses to blue light in persons with depressive disorder (2)(3)(4). With pupillometry, the pupillary contraction and dilatation in response to different wavelength light stimuli are recorded and quantified.…”
Section: Investigations Of Pupillary Responses In Depressionmentioning
confidence: 99%
“…Brief self-referral initiatives (also called brief admission, self-admission, or patient-controlled admission) have evolved as a promising alternative to lengthy and unstructured psychiatric admissions for those diagnosed with BPD (Helleman, Goossens, Kaasenbrood, & van Achterberg, 2014a), eating disorders (Strand, Gustafsson, Bulik, von, & Juhlin, 2015); schizophrenia, and bipolar disorder (Moljord et al, 2017;Sigrunarson, Moljord, Steinsbekk, Eriksen, & Morken, 2017;Thomsen et al, 2018). These structured crisis management programs are founded on predefined agreements regulating admission length and services included.…”
Section: Introductionmentioning
confidence: 99%